On a Nonlinear Heat Equation with Degeneracy on the Boundary (Journal of Partial Differential Equations, 2019)
The paper studies the stability of weak solutions of a nonlinear heat equation with degenerate on the boundary. A new kind of weak solutions are introduced.By the new weak solution, the stability of weak solutions is proved only dependent onthe initial value.
Keywords: Nonlinear heat equation; weak solution; stability; initial value.